The Makna Sakīnah dalam Al-Qur’an dan Relevansinya Terhadap Keharmonisan Rumah Tangga (Kajian Semantik Toshihiko Izutsu): Kajian Semantik Toshihiko Izutsu - Ela Sartika; Abdul WahabJunaedi (Khulasah : Islamic Studies Journal, 2026)
This study aims to analyze and explore the meaning of sakīnah using a semantic approach. By utilizing Toshihiko Izutsu’s semantic theory, this study aims to comprehensively reveal the basic and relational meanings of the word sakīnah, as well as the relevance of these meanings in fostering domestic harmony, particularly within contemporary society. This study employs a descriptive-analytical method with a semantic approach. The findings include the following: first, the word sakīnah is more commonly understood to have the basic meaning of mercy. Second, the relational meanings of “sakīnah” are closely associated with the wife, home, faith, prayer, the Prophet, and Paradise. Third, the relevance of sakīnah to harmony, particularly within families in contemporary society, requires actualizing sakīnah through mutual respect, honor, protection, and the provision of peace just as Eve provided peace to Adam as the first human. Therefore, sakīnah cannot be established if it is not grounded in faith; thus, the purpose of a household is not only to achieve sakīnah in this world but also to hope for sakīnah in the more eternal paradise.